Tongue flap for lip defects: Our experience. - Singh Sandesh Bharat; Dutta , Gouranga; G Guha (International Journal of Endorsing Health Science Research, 2021)
Background: Background: Lip defects following neoplasm surgery are usually complicated. Appropriate reconstruction is vital in improving the quality of life of such patients. In this study, we have assessed the usefulness of the dorsal/lateral tongue flap in cases of lip reconstruction. Methodology: A retrospective data of patients who reconstructed with either dorsal or lateral tongue flap between November 2015 and June 2018 was collected. Departmental Ethical clearance was done. Results: A total of four patients who underwent tongue flap reconstruction during this period were analyzed. The size of the defect following excision of the lesion ranged from 3-5.5 cm. There was no partial or total loss of flap in our series. Postoperatively all the patients had adequate mouth opening, good swallowing. Conclusion: Dorsal or Lateral tongue flap is a simple and reliable flap for lip reconstruction. It helps in providing good functional results with less morbidity.